P609 Impact of prior biologic exposure on durability of recaptured response to ozanimod during the True North open-label extension study. (30th January 2023) - Colombel, J F; Rubin, D T; Vermeire, S; Jain, A; Canavan, J B; Wu, H; Lawlor, G; Osterman, M T; Dignass, A; Regueiro, R
Abstract: Background: In the phase 3 True North (TN) study, ozanimod (OZA) 0.92 mg once daily showed efficacy and safety for up to 52 weeks in patients (pts) with moderately to severely active ulcerative colitis, and is approved for adults in the EU, US, and other countries for this indication. This analysis (data cutoff: 10 January 2022) evaluated the impact of prior biologic exposure on the long-term durability of response in pts who experienced disease relapse while on placebo (PBO) during the TN maintenance period (MP) and then recaptured response to OZA during the TN open-label extension (OLE). Methods: Responders to OZA 10-week induction therapy who were biologic-naive or exposed to prior biologics at baseline were rerandomised 1:1 to OZA (n=230) or PBO (n=227) during the TN MP. Pts who relapsed while on PBO subsequently entered the OLE and reinitiated open-label OZA in this interim OLE analysis. Symptomatic, clinical, endoscopic, and histologic endpoints were evaluated by observed case (OC) and nonresponder imputation (NRI) analyses. Results: This analysis included 38 biologic-naive and 38 biologic-exposed pts who entered the OLE after disease relapse on PBO (median time to relapse, 13.1 and 11.2 weeks, respectively). Symptomatic clinical response based on NRI was achieved by 26/38 (68.4%) of biologic-naive and 20/38 (52.6%) of biologic-exposed pts 5 weeks after restarting OZA in the OLE. Symptomatic clinical response by OC analysis at OLE Week 5 was achieved in 72.2% (26/36) and 55.6% (20/36) of biologic-naive and -exposed pts, respectively. Although a greater proportion of biologic-naive vs -exposed pts completed OLE Week 94 (65.8% vs 39.5%), OC rates of symptomatic clinical response at OLE Week 94 were similar (biologic-naive: 95.0% [19/20] vs biologic-exposed: 100.0% [13/13]). Key clinical, endoscopic, and histologic endpoints are shown in Fig 1. Durability of response between OLE Weeks 46 and 94 was similar in biologic-naive (40%–56%) vs -exposed pts (50%–67%) but varied depending on endpoints (NRI analysis). Reductions in mean [SD] total Mayo score were similar and sustained through OLE Week 94 in biologic-naive and -exposed pts (OLE Week 0: 8.9 [1.8] and 9.3 [1.6], respectively; OLE Week 46: 2.3 [1.7] and 4.2 [2.6], respectively; OLE Week 94: 2.6 [2.0] and 2.6 [1.4], respectively) (Fig 2). Conclusion: In pts who lost clinical response after OZA treatment withdrawal, symptomatic clinical response was recaptured within 5 weeks of OZA reinitiation in the majority of pts, and clinical benefit was maintained for up to 94 weeks (extent of current analysis) in biologic-naive and -exposed pts. This suggests that in clinical practice, pts who experience a disease relapse after temporarily holding OZA may benefit from resumption of OZA.